Benzodithienyl Silanes for Organic Electronics: AIE Solid‐State Blue Emitters and High Triplet Energy Charge‐Transport Materials. Issue 22 (22nd September 2020) - Bossi, Alberto; Arnaboldi, Serena; Castellano, Carlo; Martinazzo, Rocco; Cauteruccio, Silvia
Abstract: A novel class of benzo[1, 2‐ b :4, 3‐ b ′]dithienyl (BDT) silanes 1 –3 in which a tetrahedral silicon atom connects two BDT units is developed as high triplet energy 3D‐host. The photophysical and electrochemical properties of these structures are investigated, demonstrating that the peculiar features of the constituting BDT units are preserved in the corresponding silanes. All compounds display deep UV absorption ( Eg = 4.10–3.52 eV) and fluorescent emission (300–400 nm for 1 and 2, and 350–450 nm for 3 ). Phosphorescence is observed at low temperature and the respective T 1 states set at 2.65, 2.59, and 2.25 eV. Emission efficiency in solution is as high as 0.18 in 3 . Compound 1 crystallizes in two monoclinic structures without relevant intra‐inter‐molecular contacts; both display similar and intriguing aggregation induced emission‐like deep blue emission (390–397 nm) with quantum yield up to 13%. A blue and a green emissive organic light emitting diode devices are realized using silane 1 as semiconductive host material. The perfect sensitization of the green Ir(ppy)3 emitter results in a device which nicely compares, in terms of efficiency, with a standard one. The blue FIrpic emitter is instead only partially sensitized on account of the too closed triplets. Abstract : Bis‐benzodithienyl silanes are inherently 3D frameworks owing to the tetrahedral geometry of the Si atom. In this paper, three novel structures are prepared and fully characterized; the parent silane, which displays efficient deep‐blue luminescence in solid state, is demonstrated to be an effective, nitrogen‐free, host material for blue and green vacuum‐processed organic light emitting diodes.